Pengaruh Variabel Makroekonomi terhadap Indeks Saham Syariah di Indonesia: Model ECM - Yudhistira Ardana (Faculty of Economic and Business, 2016)
The Impact of Macroeconomics Variables to Islamic Stock Index in IndonesiaThis research aim is to analyze the impact of macroeconomics variable to Islamic stock’s index in Indonesia. The macroeconomic variables are BI-rate, inflation, foreign exchange, sharia Bank of Indonesia certificate and oil world price. The methods that used in this research is error correction model to analyze the short-run and long-run impact of macroeconomics variables to Islamic stock’s index. The result shown that the foreign exchange rate and sharia Bank of Indonesia certificate influence the to Islamic stock’s index in short-run. Otherwise the interest rate, shariah Bank of Indonesia certificate, and oil world price influence the to Islamic stock’s index in long-runDOI: 10.15408/ess.v6i1.3118